1982
DOI: 10.1029/rs017i003p00503
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electromagnetic wave propagation in multilayered media using dyadic Green's functions

Abstract: The propagation of electromagnetic waves in media with various horizontal layers has been analyzed. The electromagnetic fields outside the source region were obtained from the dyadic Green's functions for the case of media with three and four layers and for horizontal and vertical electric dipoles. These results agree with those obtained using Hertz potentials. One of the major results is a generalization of the dyadic Green's functions for solving the problem of media with N horizontal layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…(marked by N in Figure 12). The transmission factor (T) and reflection factor (R) of electromagnetic waves are considered to be the same as those at normal incidence by equations (5a) and (5b) (Dos Santos Cavalcante et al, 1982).…”
Section: Simulation With the Transmission Line Modelmentioning
confidence: 99%
“…(marked by N in Figure 12). The transmission factor (T) and reflection factor (R) of electromagnetic waves are considered to be the same as those at normal incidence by equations (5a) and (5b) (Dos Santos Cavalcante et al, 1982).…”
Section: Simulation With the Transmission Line Modelmentioning
confidence: 99%
“…(23) we found that as the number of meshes grows, the scattering cross section calculated by the collection of meshes in Eq. (25) converges to the initial value of one single mesh of Eq. (26).…”
Section: -3mentioning
confidence: 99%
“…11,[24][25][26][27][28][29][30] Our first task in this section is to arrive at an explicit expression for the scattered electric far field. This is attained by propagating the field induced by a dipole density P (1) (r ) = ε E r (r ) (where ε = ε − 1) inside the area of a ridge, to a point R very far from the source.…”
Section: Scattering Coefficientsmentioning
confidence: 99%
“…However, as first pointed out by Sommerfeld [1964], in order to satisfy the interfacial conditions in a layered medium, the vector potential used by MPIE due to vertical current source (perpendicular to layer interfaces) must be different from that due to a horizontal current source. Thus, a choice has to be made for the dyadic Green's function between the Sommerfeld potential and transverse potential [dos Santos Cavalcante et al, 1982;Michalski and Zheng, 1990;Cai and Yu, 2000]. To remedy the problem, the use of transverse electric/ magnetic (TE/TM) scalar potentials can provide the complete solution for a layered medium without strolling between these two types of dyadic Green's functions as shown by YlaOijala et al [2001].…”
Section: Introductionmentioning
confidence: 99%